2004
DOI: 10.2337/diabetes.53.4.955
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Severity of Hypoglycemia and Glycemic Lability in Type 1 Diabetic Subjects Undergoing Islet Transplantation

Abstract: Currently, the major indications for solitary islet transplantation are recurrent severe hypoglycemia and labile glucose control. Quantifying these problems remains subjective. We have developed a scoring system for both hypoglycemia and glycemic lability, established normative data, and used them in patients who have undergone islet transplantation. A composite hypoglycemic score (HYPO score) was devised based on the frequency, severity, and degree of unawareness of the hypoglycemia. In addition, using 4 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
230
1
10

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(244 citation statements)
references
References 28 publications
3
230
1
10
Order By: Relevance
“…The modified LI and the average daily risk range (ADRR) showed higher concordance with other glycemic lability indexes than did the LI or mean amplitude of glycemic excursions (MAGE). The results showed that the hypoglycemic indexes in this study population were lower than the results from Ryan et al Furthermore, the ADRR or modified LI were better measures for high risk of severe lability than were the LI and MAGE.Key words: Glycemic lability, Type 1 diabetes mellitus, Hypoglycemia center comparison as well as to establish standards for pancreas or islet transplantation [7]. Several indexes have been proposed for glycemic lability and hypoglycemia.…”
contrasting
confidence: 47%
See 2 more Smart Citations
“…The modified LI and the average daily risk range (ADRR) showed higher concordance with other glycemic lability indexes than did the LI or mean amplitude of glycemic excursions (MAGE). The results showed that the hypoglycemic indexes in this study population were lower than the results from Ryan et al Furthermore, the ADRR or modified LI were better measures for high risk of severe lability than were the LI and MAGE.Key words: Glycemic lability, Type 1 diabetes mellitus, Hypoglycemia center comparison as well as to establish standards for pancreas or islet transplantation [7]. Several indexes have been proposed for glycemic lability and hypoglycemia.…”
contrasting
confidence: 47%
“…The LI measures the severity of glycemic lability and complements the clinical assessment of patients before islet transplantation [7,12]. The LI is calculated based on the change in glucose level over a four-week period; however, the LI can change depending on the frequency of glucose measurements [13].…”
Section: Measurements and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work from Edmonton, Alberta, clearly demonstrates that intrahepatic transplantation of isolated pancreatic islets can eliminate the development of severe hypoglycemic episodes in patients with type 1 diabetes (2). Islet transplantation may abolish hypoglycemia by reducing exogenous insulin requirements, but whether improvement in glucose counterregulatory mechanisms against hypoglycemia also contributes has not been fully studied.…”
mentioning
confidence: 99%
“…Chez les premiers patients, durant la première année qui a suivi la greffe, la glycémie s'est normalisée, leur permettant d'éviter le recours à l'insuline. Toutefois, cinq années plus tard, seuls 10 % des patients greffés sont restés indépendants d'un apport d'insuline exogène [3]. Ces données encourageantes ont entraîné la mise en place d'importants programmes de greffes d'îlots dans le monde.…”
unclassified